2021
DOI: 10.3389/fonc.2021.658138
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Growth Rate of Early-Stage Lung Adenocarcinoma by Radiomics

Abstract: ObjectivesTo investigate the value of imaging in predicting the growth rate of early lung adenocarcinoma.MethodsFrom January 2012 to June 2018, 402 patients with pathology-confirmed lung adenocarcinoma who had two or more thin-layer CT follow-up images were retrospectively analyzed, involving 407 nodules. Two complete preoperative CT images and complete clinical data were evaluated. Training and validation sets were randomly assigned according to an 8:2 ratio. All cases were divided into fast-growing and slow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Similar to our study, Tan et al 39 divided pulmonary nodules into the fast-growth group (VDT ≤400 d) and slowgrowth group (VDT > 400 d), and radiography, radiomics, and radiography combined radiomics models were established using the decision tree to predict VDT. The AUC in the test set was 0.727, 0.710, and 0.78, respectively.…”
Section: Discussionsupporting
confidence: 53%
“…Similar to our study, Tan et al 39 divided pulmonary nodules into the fast-growth group (VDT ≤400 d) and slowgrowth group (VDT > 400 d), and radiography, radiomics, and radiography combined radiomics models were established using the decision tree to predict VDT. The AUC in the test set was 0.727, 0.710, and 0.78, respectively.…”
Section: Discussionsupporting
confidence: 53%
“…Several studies ( 34 ) have demonstrated that radiomic signatures can differentiate malignant and benign nodules with a sensitivity ranging from 76.2 to 92.9% and a specificity ranging from 72.7 to 96.1%. The combined radiographic factor or supervised machine learning with the radiomics model could achieve better performance ( 34 , 35 ). In the traditional radiomics methods to classify pulmonary nodules ( 11 ), large amounts of labor are required for manual tumor segmentation and feature extraction.…”
Section: Discussionmentioning
confidence: 99%
“…The enrolled patients were randomly divided into a training set and a validation set at a ratio of 8:2 using SPSS software (version 25.0; IBM Corp., Armonk, NY, USA). This ratio is the one that is commonly used to divide training and validation datasets (20)(21)(22). Univariate analysis was conducted to identify meaningful candidate variables for the model.…”
Section: Construction and Validation Of The Modelmentioning
confidence: 99%